FINANCIAL MANAGEMENT OF NAGARI OWNED ENTERPRISES (BUMNAG) AND ITS IMPACT ON COMMUNITY WELFARE - Dandi Aprila; Wiwik Andriani; Rangga Putra Ananto (Jurnal Akuntansi Bisnis, 2023)
Background: Based on the initial observations that have been made, it was found that the application of the principle of transparency in the management of BUMNag in Nagari X had not been appropriately implemented because many programs from BUMNag were unknown to the public even though the program was already running. This is caused by the need to disseminate information to the public by BUMNag. Then, based on data accessed through the official Nagari website, there have yet to be any financial reports that the public can access. Furthermore, based on observations, no vision and mission of BUMNag could describe the commitment of BUMNag in Nagari X. The governance of BUMNag should pay attention to applying the principle of transparency to information as a form of accountability to the public. The duties and responsibilities carried out by BUMNag in Nagari X have yet to be carried out following the rules stipulated in Dharmasraya Regent Regulation Number 42 of 2018 concerning Nagari-Owned Enterprises. A business entity, if managed properly, will certainly be able to provide benefits to various parties and can have a positive influence on village development, community welfare, and others.Purpose: This study aims to determine and explain the influence of accountability, transparency, and organizational commitment in managing Nagari-Owned Enterprises (BUMNag) funds on people's welfare.Research Method: The research method uses a quantitative approach. The population in this study is the strata of society in Nagari X. The selection of samples was made by stratified random sampling technique with 98 respondents.Research Results: The results showed that accountability, transparency, and organizational commitment in the management of Nagari-Owned Enterprises (BUMNag) funds positively improved community welfare.Novelty: This research is the first study to discuss the financial management of BUMNAg and its impact on people's welfare using qualitative methods.